Pengaruh Media Elektronik TV Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PKn Kelas V SD Inpres Sero’ Kecamatan Somba Opu kabupaten Gowa - Nasrun Hasan; Andi Baso (JED (Jurnal Etika Demokrasi), 2017)
The purpose of this research is to know how big influence of TV electronic media to student learning result of Civics. The study was conducted in Sero elementary school in Somba Opu district of Gowa district by selecting 60 students as sample, while data collection using libraly method, school observation and assessment of learning result with instrument sheet about pretest and post test. The data collected were analyzed using descriptive techniques to describe the characteristics of the distribution of scores of the control class and experimental class and inferential analysis techniques (experiments) type of t test analysis to test the hypothesis. The result of the research shows that the result of the comparison of the coefficient of the average value of checklist (observation) on the students' learning result (t arithmetic) between the experimental class (X2) and the control class (Y2) is 2.49 bigger than t table at significant level 95% ie 1, 70, then the hypothesis is accepted. Based on the analysis results, it can be concluded that there is a significant influence on the use of TV electronic media on the ability to understand the importance of the Unitary State of the Republic of Indonesia in grade V SD Inpres SeroKecamatan Somba Opu Gowa District.Keywords: Electronic Media TV. Civic learning outcomes.